Exploring the Role of Volunteer Organizations in Developing Italy’s Community-Based Care Model - Federico De Luca; Giuliana Costa; Cristina Masella (International Journal of Integrated Care)
Introduction: Community-based healthcare models are crucial for reforming primary care delivery and integrating prevention, health promotion, and care services within communities. Volunteer organizations are increasingly recognized for their potential contributions; however, their integration within Italy’s emerging Community Health Center (CHC) model still needs to be explored. This study investigated the role of volunteer organizations in developing Italy’s CHC model by focusing on how these groups can enhance care coordination and community health outcomes. Methods: A qualitative descriptive approach was employed, combining semi-structured interviews and focus groups with key stakeholders, including CHC managers, primary care directors, social service providers, and volunteer organization representatives in the Piacenza area of Emilia Romagna. Data collection spanned July 2021 to March 2022, and thematic analysis was used to identify core themes related to the integration of volunteer organizations in CHCs. Results: The study identified four key areas where volunteer organizations contribute: (i) prevention and health promotion, (ii) identifying unmet needs and caregiver support, (iii) collaborative initiatives between CHCs and volunteers, and (iv) creating spaces for teamwork. Despite these contributions, challenges related to organizational coordination, limited operational specialization, and geographic disparities have been noted. Volunteer organizations were found to play a critical role in addressing gaps in community services, yet their involvement in CHC planning and execution varied across territories. Discussion: Although volunteer organizations have the potential to significantly enhance community-based care, their integration into Italy’s CHC model is hindered by limited coordination, funding constraints, and uneven involvement across regions. Strengthening partnerships, improving operational support, and creating dedicated collaboration spaces are essential to fully leveraging their contributions. Future research should explore strategies for enhancing the sustainability and scalability of volunteer-led initiatives within the CHC framework.